Status and Challenges of LGBTI in Nepal - Acharya, Suresh (Rural Development Journal, 2019)
LGBTI stands for lesbian, gay, bisexual, transgender and intersex. Lesbians are women who experience sexual or emotional attraction to other women. Gays are men who feel sexually or emotionally drawn to other men. Bisexuals are those who are sexually or emotionally attracted to both men and women, or to two or more genders among the various gender identities. Transgender individuals have a gender identity or expression that differs from the sex they were assigned at birth. Intersex individuals possess sexual anatomy that does not fit typical definitions of male or female biology. Sexual orientation is a crucial aspect of a person’s identity and encompasses lesbian, gay, bisexual, transgender, and intersex identities. This study examines the status of LGBTI individuals in Nepal, utilizing secondary data gathered from literature such as books, journals, and newspapers. The findings indicate that Nepali society is deeply entrenched in patriarchal values. While heteronormativity has historically prevailed, the society is gradually becoming more sensitive to the needs of the LGBTI community. The struggle for equal rights and acceptance for LGBTI individuals in Nepali society is extensive and begins early in life, as heteronormative expectations are imposed from a young age. This research aims to provide a better understanding of the situation of LGBT individuals in the Nepali context.